1999
DOI: 10.1172/jci6093
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of arthritic bone destruction by adenovirus-mediated csk gene transfer to synoviocytes and osteoclasts

Abstract: Rheumatoid arthritis (RA) is characterized by a chronic inflammation of the synovial joints resulting from hyperplasia of synovial fibroblasts and infiltration of lymphocytes, macrophages, and plasma cells, all of which manifest signs of activation. Recent studies have revealed the essential role of osteoclasts in joint destruction in RA. Src family tyrosine kinases are implicated in various intracellular signaling pathways, including mitogenic response to growth factors in fibroblasts, activation of lymphocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
75
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(82 citation statements)
references
References 47 publications
7
75
0
Order By: Relevance
“…We previously observed that Src activation in vivo can be detrimental (19). Csk-expressing adenovirus, which inhibits Src by phosphorylation of Tyr 527 , has been shown to block apoptotic signaling (20,21). Csk also influences paxillin phosphorylation (22)(23)(24), although the cellular impact of this regulation remains to be elucidated.…”
mentioning
confidence: 99%
“…We previously observed that Src activation in vivo can be detrimental (19). Csk-expressing adenovirus, which inhibits Src by phosphorylation of Tyr 527 , has been shown to block apoptotic signaling (20,21). Csk also influences paxillin phosphorylation (22)(23)(24), although the cellular impact of this regulation remains to be elucidated.…”
mentioning
confidence: 99%
“…These include interference with the Ras-Raf MAPK pathway (Jorgensen & Gay 1998) and inhibition of the Src tyrosine kinase (Takayanagi et al 1999). These have been implicated in several biological functions, including mitogenic response to growth factors and cytokines, activation of lymphocytes and osteoclastic bone resorption.…”
Section: Inhibition Of the Inflammatory Response By Disrupting Specifmentioning
confidence: 99%
“…The kinase activity of Src is negatively regulated by phosphorilation with another cytoplasmic tyrosine kinase named Csk (Cterminal Src kinase). Adenovirus-mediated overexpression of Csk tyrosine kinase dramatically reduced the proliferation rate and inflammatory activity in the joint by suppressing Src activity and almost completely repressed the bone-resorbing activity of osteoclasts (Takayanagi et al 1999). Recently, Taniguchi et al (1999) have also shown that cyclin-dependent kinase inhibitors, such as p16 INK4a gene can be used by gene transfer to suppress synovial cell proliferation.…”
Section: Inhibition Of the Inflammatory Response By Disrupting Specifmentioning
confidence: 99%
See 1 more Smart Citation
“…Pannus releases several proinflammatory mediators, matrix metalloproteinase (MMP), immune modulatory factors and bone metabolism-related factors [27]. It was thought that osteoclastogenesis is enhanced by release of factors such as ILs, TNF-a and receptor activator of nuclear factor-kappa B ligand (RANKL) from pannus [23]. Activated osteoclasts have been shown to stain for tartrate-resistant acid phosphatase [25].…”
Section: Introductionmentioning
confidence: 99%